(untitled) (Contemporary Journal of Social Science Review, 2025)
Social media influences deeply influence digital communication because their language selections determine how much interaction their audience will show. The research explores the linguistic approaches which Pakistani influencers utilize through Instagram Stories for engaging both male and female audience members. The research bases its analysis on Tannen’s Socio-Cultural Theory (1990) to study the gendered linguistic elements in hedges, intensifiers, tag questions, assertive statements and politeness markers across Instagram captions, overlays and hashtags. The research investigates ten Pakistani influencers’ Instagram content through qualitative content analysis by evaluating both male (five) and female (five) creators. Researchers observed separate communication behaviors between men and women. Both male influencers Shahveer Jafry and Junaid Akram showcase direct language style featuring assertiveness through messages about ambition along with resilience and competitive outlook. Female social media influencers such as Waliya Najib and Hira Bleeh utilize emotionally charged and communicative language which incorporates transitional language with amplifiers while expressing gratitude to build interpersonal bonds with their audience. The study delivers beneficial knowledge about audience behavior toward social media content since it reveals how language strategies shape user interactions. Marketing professionals should understand gendered communication patterns because this knowledge helps create targeted successful online marketing campaigns. This study has valuable insight for the social media marketers and influencers in making the content tailored to their audience. The study can be extended in the future to include how the cultural trends and digital platforms shape gendered communication patterns in the various areas.